Design of filter integrated SPDT switch using capacitor loaded ring resonator with high isolation - Shairi, Noor Azwan; Nasser, Zayed Abdo Abdullah; Zakaria, Zahriladha; Zabri@Suhaimi, Siti Normi; Zobilah, Abdullah Mohammed Saghir; Alwareth, Husam Abdulqudos Ahmed (The Electromagnetics Academy, 2022)
A reconfigurable filter integrated single-pole double-throw (SPDT) switch (FIS) based on capacitor loaded ring resonators is presented in this paper. The design incorporates two PIN diodes between two symmetric square ring resonators. The ring resonators can be switched between all stop and bandpass responses, by adjusting the state of the PIN diodes, allowing the corresponding signal path to be in OFF-state with high isolation or ON-state with bandpass filter response. For demonstration, filtering switch was fabricated and measured for 2.4 GHz applications. The measurement results featured an ON-state low insertion loss of −2.1 dB and port-to-port isolation of −52 dB at the band of interest, and good consistency is achieved between simulated and measured results